Reestablishment of the name Piptolepis pseudomyrtus (Vernonieae, Asteraceae) - Cândido, Jacqueline B.; Loeuille, Benoît (Phytotaxa, 2022)
In the course of a taxonomic revision of the genus Piptolepis (Vernonieae, Asteraceae), it became clear that P. pseudomyrtus, until now considered a synonym of P. buxoides, should be re-established. It differs from P. buxoides by its habit, leaf shape, number of florets per head, cypsela shape, and length of pappus series. An updated morphological description, geographic distribution, illustration and conservation status of P. pseudomyrtus are provided, as well as a comparative discussion with P. buxoides.